Empowering Cattle Keepers for On-Farm Production and Utilization of Green Fodder and Planting Materials: Hybrid (HB) Napier (Pennisetum Purpureum) in Sitapur District of Uttar Pradesh - Shantanu Kumar Dubey, U.S. Gautam, Atar Singh, Anand Singh; Anand Singh (Indian Journal of Extension Education, 2018)
An action oriented field study was conducted among 30 rural youths of five villages in Biswan block of Sitapur district in Uttar Pradesh. The selected rural youths were facilitated for utilizing Hybrid (HB) Napier grasses for production of green fodder and rooted slips during rainy and winter seasons. The on-farm assessment trials were conducted across five villages among the selected youth with twofold objectives to see the utilization of Hybrid Napier grasses for green fodder purpose as well as enabling them for rooted slips production. The research variables included seasonal adaptability of the rooted slips, differential seasonal performance, technoeconomic feasibility of utilizing the HB Napier for green fodder and rooted slips production and potential windows for better utilization of the rooted slips produced on-farm. Results showed better adaptability of rooted slips HB Napier in winter (60 days) as compared to rainyseason (30 days). However, on all other technical parameters and yield of rainy season (900-1000 q/ha/year) harvest out rated the winter season (600-700 q/yr/ha). The B:C ratio for rooted slips production was found 3.1 compared to 6.31 for green fodder production using HB Napiers.The necessary institutional arrangements and stakeholders’ partnership for out scaling this promising technology has been discussed.